METODOLOGI TAFSIR - Rohman, Ali Abdur (Jurnal al Hikmah, 2016)
This article discussed about methodology of interpretation. On fundamentally the methodology was discussion about method and procedure to solve a problem in the research or writing. For thus methodology was the primary apparatus that couldânt discharged from interpretation of the Qurâan. In order that the Qurâan could to function as the aim descended, that is guidelines (hudan), so the Qurâan must learned and tried his interpretation. Since the Qurâan descen era always show up the interpretation and then stab all kinds atmosphere or Islamic scientific knowledge that collaborate with development of the humans culture, the Qurâan always qualified for every time and place (s{a>lih{ li kulli al-zama>n wa al-maka>n). This was proved by appeared various of the tafsir book that had various of formulaition, replica, and the interpretation resource. In interpretation of Qurâan interpreters had construct the interpretation frame according to syistematically, that was ijma>li> (golbal), tah{li>li> (analysis), muqa>rin (comparison), and maud}u>âi> (thematic). And then according to the interpretation resource, that was al-maâsu>r (transmittion), al-raâyu (ratio), al-isya>ri> (indicative). Thus, the article was as effort to describe these method that included in study of âthe interpretation methodologyâ.